Answer:
The proof itself
Explanation:
We can define the set of all even numbers as
![E = \{ a \in \mathbb{Z} \setminus a = 2.k , k\in \mathbb{N}\}](https://img.qammunity.org/2020/formulas/mathematics/college/mopzgm0at1fm7i9you20rrrokgrlw6q20x.png)
This is, we can define all even numbers as the set of all the multiples of
![2](https://img.qammunity.org/2020/formulas/mathematics/high-school/ungpj0wd9ftsqhaos5e4zdvweyb227ctto.png)
As for the odd numbers, we can always take every even number and sum one to each one. This is
![O = \{ a\in \mathbb{Z} \setminus a=2.k+1,k\in\mathbb{N}_(0)\}](https://img.qammunity.org/2020/formulas/mathematics/college/8m67ohleww2drn1ahyjov43sclyj3zatvr.png)
Note that
(the set of all natural numbers adding the zero) so that for
then
![a=1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/krkbqffkhyhi4myj6mrpvfi4x1hu9srce5.png)
Now, given 2 odd numbers
and
we can write each one as follows:
![a = 2k+1\\b = 2l+1\\k,l \in\mathbb{N}_(0)](https://img.qammunity.org/2020/formulas/mathematics/college/o5ejy7ki3gmlasi905aq5xq69l8jeuzjz2.png)
And then if we multiply them with each other we obtain:
![a.b = (2k+1).(2l+1)\\= 4kl+2k+2l+1\\= 2(2kl+k+l) + 1\\= 2k'+1 \\where\ k'=2kl+k+l](https://img.qammunity.org/2020/formulas/mathematics/college/9jddu8evkystodv8e77aav82ca1bwp0am3.png)
Then we have that
is also an odd number as we defined them.